CHANGES IN IMPACT FACTOR - Sen, B.K. (Malaysian Journal of Library and Information Science, 1999)
Enumerates some conditions that affect the impact factor of a standard research journal to undergo change. Shows with mathematical proof that the impact factor of a journal will tend to increase or decrease with the increase or decrease in the number of standard research journals covered by a database, or with a substantial change in the composition of content of a journal. The inclusion of more articles of higher citation generation potential will tend to increase its impact factor and lower citation generation potential will tend to bring it down.